Geochemical sedimentary evolution during process of mangrove forest formatio, development and degradation in red river mouth (on example of Giao Thuy mangrove forest, Nam Dinh province) - Ngoc, Nguyen Thi Minh; Nhuan, Mai Trong; Luyen, Dang Van (VNU Journal of Science: Natural Sciences and Technology, 2004)
In tropical littorals, thanks to coastal sedimentation, low tidal mudflats tend to be elevated into high tidal mudflats, which are more favorable for keeping and storing mangrove seeds (Hoekstra, 2000) [10]. But when the mudflats become higher than the spring tide level, mangrove forest (MF), which is under dominant influence of fresh water, begins degrade. In several coastal regions of Vietnam, the degradation of mangrove forest is also caused or intensified by human making aquacultural ponds. Environmental variations during the process of formation, development and degradation of mangrove forests are recorded in the sediment profiles of these regions in the manner of sedimentary, geochemical and nutritional tendencies. Interpretation of these geochemical records in coastal sediment will be a contribution to reconstruct the environmental evolution of the process of mangrove forests formation, development and degradation in the Red River mouth,(Giao Thuy mangrove forest), Nam Dinh province (Figure 1).